The public sector pay gap in a selection of Euro area countries - Raffaela Giordano; Domenico Depalo; Manuel Coutinho Pereira; Bruno Eugène; Evangelia Papapetrou; Javier J. Pérez; Lukas Reiss; Mojca Roter (European Central Bank (ECB), 2011)
We investigate the public-private wage differentials in ten euro area countries (Austria, Belgium, France, Germany, Greece, Ireland, Italy, Portugal, Slovenia and Spain). To account for differences in employment characteristics between the two sectors, we focus on micro data taken from EU-SILC. The results point to a conditional pay differential in favour of the public sector that is generally higher for women, at the low tail of the wage distribution, in the Education and the Public administration sectors rather than in the Health sector. Notable differences emerge across countries, with Greece, Ireland, Italy, Portugal and Spain exhibiting higher public sector premia than other countries.
Keywords: J31; J45; O52; 330; public/private sector; Wage differentials